Analisis Determinan Tingkat Pengangguran Terbuka di Pulau Jawa Tahun 2007-2016 - Wildan Aziz Amrullah; Nanik Istiyani; Fivien Muslihatinningsih (UPT Penerbitan Universitas Jember, 2019)
Unemployment is a complex problem because it's affecting and influenced by many factors that interact with each other following patterns that are not easy to understand. The problem of unemployment is the one result of the existence of economic phenomena that occur. The rate of unemployment can be influenced by several indicators, such as the amount of prevailing wage, The GDP, and inflation rate. The aim of this research is to know how big influence of the GDP, Province Minimum Wage and inflation rate on open unemployment in every province in Java Island Year 2007-2016. The method analysis of this research using Panel data with using Fixed Effect Model (FEM) approach. The result of panel data regression showed simultaneously that the variables of tghe GDP, Province Minimum Wage, and inflation have significant, The result of partial test analysis showed that The GDP has significant influence, while province Minimum Wage and inflation have a negative and insignificant on open unemployment Rate in Java Island period 2007-2016. The total variation in open unemployment rate in Java Island province can be explained by independent variables of PDRB, UMP and inflation at 93.35%. Keywords: Open Unemployment Rate, The GDP, Province Minimum Wage, Inflation.